Role of pH and Kepok Banana Peel Pectin in ?--Tricalcium Phosphate Formation from Windowpane Oyster (Placuna placenta) Shells - Muhammad Taqiyyuddin; Fransisca Adya Zahiroh; Luluk Edahwati; Nur Ikhtiarini; Srie Muljani; Reva Edra Nugraha (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
?--tricalcium phosphate (?--TCP) has potential as a bone material because it is biodegradable, biocompatible, bioresorbable, and osteoconductive. This study aims to synthesize ?-tricalcium phosphate (?-TCP) from windowpane oyster shells and to determine the effect of adding kepok banana peel pectin on particle size and pH on the Ca/P ratio. Synthesis was performed with pH variations ranging from 9 to 11 and pectin concentrations of 0.08-0.16%, using a sintering time of 3 hours at 1100ºC via the precipitation method. The resulting ?-tricalcium phosphate was characterized using XRF, FTIR, XRD, and SEM analyses. XRF results showed that variations in pH and pectin concentration affected the Ca/P ratio. All samples had a Ca/P ratio higher than the ?-TCP standard (1.5). XRD analysis revealed the formation of peaks identical to the JCPDS ?-TCP standard no. 09-0169. However, the formation of calcium pyrophosphate (CPP), hydroxyapatite (HAp), and calcium oxide (CaO) phases was also observed in the results of this study. XRD analysis yielded an average crystal size of 37.48 nm and a degree of crystallinity of 53.55%. FTIR results for all samples showed characteristic phosphate group bands consistent with the ?-TCP phase. SEM characterization showed that at pH 10 with the addition of 0.12% pectin, the morphology ranged from semi-spherical to granular with relatively uniform particle size and low agglomeration, with an average particle size of 1.8237 ?m and a PDI of 0.08. The sample at pH 10 and a concentration of 0.12% exhibited the highest crystallinity and the smallest particle size. Although the Ca/P ratio did not meet the standard, it was 2.03, the XRD and FTIR test results confirmed the presence of phases and groups identical to those found in ?-TCP. Contribution to Sustainable Development Goals (SDGs):SDG 3: Good Health and Well-BeingSDG 9: Industry, Innovation, and InfrastructureSDG 12: Responsible Consumption and ProductionSDG 13: Climate ActionSDG 14: Life Below Water